Sensitivity assay of Alternaria alternata from citrus in China to four new fungicides - HE Meixian; FU Yushi; RUAN Ruoxin; LI Hongye (浙江大学学报. 农业与生命科学版)
Alternaria brown spot (ABS), an emerging disease in China, is caused by Alternaria alternate pv. citri (A. alternata pathotype tangerine). The disease mainly affects tangerine and tangerine hybrid citrus, causing young leaf drop, fruit drop and dieback, and resulting in yield loss and affecting the commodity of fruits. ABS was first reported in Australia in 1962 and has become a serious problem in many citrus producing areas in South America, Florida, South Africa, Spain, Israel, Turkey and other countries in the Mediterranean area. ABS was first reported in China in 2010, affecting many important citrus varieties grown in Chongqing, Zhejiang, Yunnan, Hunan, Guangdong, Guangxi and Sichuan and causing significant yield losses. ABS can be controlled by fungicides; however, there is no existing fungicide that is currently registered for controlling ABS on citrus in China. In order to identify effective fungicides for controlling ABS, an in vitro sensitivity assay was conducted. In total, 54 isolates of A. alternate pv. citri were single-spore collected from citrus-producing areas in Chongqing, Yunnan, Hunan, Zhejiang, Guangdong and Guangxi Provinces and were tested for sensitivity to fungicides, including boscalid, flutolanil, thifluzamide and fluazinam using a rapid Resazurin-based microtiterplate assay. Conidia were induced by growing fungal strains on V8 medium at 25℃ with 16 h light/8 h dark cycle for 7 to 10 days. The concentration for 50% of maximal effect (EC50) of spore germination and mycelium was established for each isolate. All test isolates were sensitive to tested fungicides in varying degrees. In general, all isolates were highly sensitive to flutolanil, thifluzamide and fluazinam with an average EC50 of 0.010 3 μg/mL, 0.061 9 μg/mL and 0.010 0 μg/mL, respectively. When tested with boscalid, isolates had EC50 ranging from 0.238 3 μg/mL (C14 isolate collected from Chongqing) to 0.858 5 μg/mL (Z11 from Zhejiang) with an average of 0.467 7 μg/mL. It was observed that fungal strains collected from Guangdong and Zhejiang were less sensitive to boscalid than other test isolates, and strains collected from Chongqing were more sensitive to thifluzamide than others. However, there was no correlation between the sensitivity to flutolanil and fluazinam and geographical origin of the isolates.Overall, our studies revealed that boscalid, flutolanil, thifluzamide and fluazinam were effective for suppressing A. alternate pv. citri in vitro. It will be imperative to conduct field experiments for controlling ABS. The EC50 values obtained from this study could be used as baselines for monitoring the development of fungicide-resistant subpopulation in future.